A Review of Nephrotoxins and Their Mechanism of Nephrotoxicity - Sahu, Vaishnavi; Panjwani, Dharamveer; Mishra, Vibha (Current Functional Foods, 2024)
The harmful impact of substances on renal function is known as nephrotoxicity and the substance that shows a harmful impact is called nephrotoxins. Nephrotoxins can be classified into various categories like drugs as nephrotoxins, plant-origin nephrotoxins, environmental toxins, dietary supplements as nephrotoxins, mycotoxins, pesticides and some infection-causing agents to act as nephrotoxins. Drugs like cisplatin and aminoglycosides, plants like lemongrass and licorice, pesticides like alachlor and atrazine, environmental toxins like heavy metals, halogenated aliphatic hydrocarbons and aromatic halides, mycotoxins like citrinin are the examples of nephrotoxins. The various mechanisms by which they can cause nephrotoxicity are inflammation, tubular cell necrosis (drug-induced), hemolysis, vasoconstriction (plant-induced), oxidative stress, enhanced permeability, encephalopathy (environmental toxins), cysts formation, nephrolithiasis (by dietary supplements), tubular epithelial degeneration, vascular congestion (pesticides induced) endothelial cell damage, hypertrophy of tubular cell, increased vascular permeability (infection agents induced), etc. The abstract provides an overview of the basic groups of nephrotoxins as well as specific examples and their individual modes of action. It also emphasises the great diversity of substances and mechanisms that can contribute to nephrotoxicity.
Keywords: dietary supplements